Conversion of methyl ketones and methyl sulfones into α-deutero-α, α-difluoromethyl ketones and α-deutero-α, α-difluoromethyl sulfones in three synthetic steps. Issue 5 (1st February 2017) - Sowaileh, Munia F.; Han, Changho; Hazlitt, Robert A.; Kim, Eun Hoo; John, Jinu P.; Colby, David A.
Graphical abstract: Highlights: Deuterodifluoromethyl ketones and sulfones are prepared in three synthetic steps. High levels of deuterium on the "CF2 D" group are observed. Over- and under-fluorinated by-products are not isolated using this process. Abstract: Deuterodifluoromethyl ketones and sulfones were assembled in three synthetic steps from methyl ketones and sulfones, respectively. The key synthetic transformation is the deuteration of the difluorocarbanion generated by the release of trifluoroacetate from highly α-fluorinated gem-diols. High levels of deuterium on the "CF2 D" group were routinely observed. This strategy is mild and versatile and it can be applied to both ketones and sulfones without additional concerns of over- or under-fluorination. Additional examples address issues of over-deuteration when compounds with other acidic protons are subjected to the reaction conditions. This process not only demonstrates a new method to install a "CF2 D" group but also extends the scope of trifluoroacetate release to sulfones.